Hierarchical frequency control framework for a remote microgrid with pico hydel energy storage and wind turbine - Vasudevan K.R.; Ramachandaramurthy V.K.; Venugopal G.; Ekanayake J.B.; Tiong S.K. (Elsevier Ltd, 2023)
Agricultural robots; Electric energy storage; MATLAB; Time domain analysis; Wind; Wind turbines; Control strategies; Operation and maintenance; Operational failures; Pitch angle controller; Power management algorithms; Remote communities; Time-domain simulations; Water and energies; Microgrids